37.0k views
2 votes
What is the difference of the two polynomials (9x^2+8x)-(2x^2+3x)

2 Answers

3 votes

Distribute the negative sign:


(9x^2+8x)-(2x^2+3x)=9x^2+8x-2x^2-3x

Gather like terms:


9x^2+8x-2x^2-3x = (9x^2-2x^2) + (8x-3x) = 7x^2+5x

User Roshanpeter
by
6.0k points
2 votes

Answer:

7x² + 5x

Explanation:

Given

(9x² + 8x) - (2x² + 3x) ← distribute parenthesis, second by - 1

= 9x² + 8x - 2x² - 3x ← collect like terms

= (9x² - 2x² ) + (8x - 3x)

= 7x² + 5x

User Vijay S B
by
6.9k points